PENINGKATAN KREATIVITAS MELALUI MENGGAMBAR PADA ANAK 5-6 TAHUN PAUD PEKKA AT-TAQWA - Elinawati yarso; Muhamad Ali; Dian Miranda (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research to know the children’s creativity ability through drawing activity. The recearcher expected to be able to improve children’s creativity optimally. This research, while the method used by using deacriptive method. The research subjects were 10 children in PAUD PEKKA AT-TAQWA Kubu Raya Regency. This research used two cycles and analyzed through percentage values. The result got from the first cycle were the aspectof creativity are great curiosity 40 percent, the aspect of imagination in directed manner 40 percent, the bravery aspect 50 percent, the aspect of responsibility 50 percent. The second cycle the aspects of great curiosity 50 percent, aspect of imagination indirected manner 40 percent, the bravery aspect 60 percent, aspects of responsibility 60 percent and the aspect of confidence 50 percent. Therefore it gan be concluded that the implementation of learning through drawing can improve children’s creativity. Based on the research that has been carried out, then the researcher can suggest to the teacher to provide encouragemnt, motivition to the children. And with the gradual and continuous drawing activity given by the teacher, the children’s creativity can develop optimally. Keywords: Creativity and drawing